REPOSISI AGAMA SEBAGAI SUMBER SPIRITUALITAS MASYARAKAT MODERN - Muh. Fihris Khalid (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2017)
Advancement of Science and Technology modern society opens new insights roomates are shown to the endless emptiness And ketidakbermaknaan life. Practical operating spawned a new phenomenon for review found faith laden with spritualitas the push comes qalbu management (Aam Gym), ESQ (Ari Ginanjar) and dzikr majlis (Arifin Ilham) to review Treating spirituality crisis of modern man. Time is now Islam Introduce inner dimensions shown to the west as an alternative human need on socialized them, at least three main purpose. first, participate share hearts save humanitarian role of conditions of confusion as a result of the loss of indigo-spiritual value. Second, the literature introducing or about aspect esoteric understanding of Islam, against the modern western society. Third, to review gives confirmation that the actual return aspect esoteric Islam, ie, Sufism, Islamic teaching is heart, so If wilayah dry singer snd no longer pulsed, then dried up aspects lie Islamic teachings.